PENGARUHILINGKUNGANOPENGENDALIAN,LPENILAIANURESIKO SERTA;INFORMASI.DANKOMUNIKASIITERHADAPIKUALITAS KREDIT MIKROLDI.BRI UNIT SE-KANTOR CABANG BRI UBUD - Luh Ade Dwi Wahyuni; I Wayan Sudiana; Putu Cita Ayu (Hita Akuntansi dan Keuangan, 2021)
Credit quality is one of the most important things in the world of banking. The better the credit quality, the better the performance of the bank because credit is one of the banks biggest prÂofit sources. But in reality banks are still experiencing problems in maintaining good credit quality caused by internal and external parties of the bank. The purpose of this study was to determine the effect of the identification environment, risk assessment as well as information and communication of the quality of microcredit in the BRI of the Ubud Branch Office. To maximize credit quality the bank can implement an internal control system. This study uses descriptive quantitative data analysis, data collection as done by distributing a questionnaire to respondents. This research uses data analysis techniques: validity test, reliability test, multiple linier regression analysis, coefficient of determination, F test and t test. As for the result of the study stated the validity test show the results of the assessment above 0,05 which means that all statements in the questionnaire are valid. Reliability test shows results above 0,60 which means all of the variables are reliable. Multiple linier regression analysis showed results is X1: 0,438, X2: 0,266 and X3: 0,275. The coefficient of determination shows a figure of 65,3% which means the control environment, risk assessment and information ad communication have a 65,3% effect on credit quality while 34,7% is influenced by other factors not examined. F test and t test show the results of X1, X2 and X3 have a positive and significant effect on credit quality.